ANALISIS TAHU TERKONTAMINASI FORMALIN MENGGUNAKAN SISTEM SPEKTROSKOPI FLUORESENSI BERBASIS HIGH POWER UV-LED - Rahmaningrum, Nadia; Rakhmadi, Frida Agung; Fajriati, Imelda (Sunan Kalijaga Journal of Physics, 2020)
This research was motivated by the discovery of white tofu preserved using formalin. This study aimed to analyze formalin contaminants in tofu and determine the precision and detection limits of a fluorescence spectroscopy system based on high power UV-LED. This research was conducted in three stages, namely making samples, collecting data, and processing data. The sample was made directly in the tofu factory with the owner and the object used in this study is white tofu which was given a variation of formalin contaminants 0%-50%. Data were collected using a set of fluorescence spectroscopy system based on high power UV-LED that is connected to software LabVIEW and each foreign formalin contaminant test in tofu used five samples with three repetitions for each sample. Data processing to obtain bin values for each a variation of formalin contaminant was carried out using Microsoft Excel, moreover to find a value of precision and a detection limit. Based on the result, a precision test result of 100% and a detection limit of 12.05%.